Two-Scale Convergence of Stekloff Eigenvalue Problems in Perforated Domains. (30th November 2010) - Douanla Douanla, Hermann Hermann
Abstract : By means of the two-scale convergence method, we investigate the asymptotic behavior of eigenvalues and eigenfunctions of Stekloff eigenvalue problems in perforated domains. We prove a concise and precise homogenization result including convergence of gradients of eigenfunctions which improves the understanding of the asymptotic behavior of eigenfunctions. It is also justified that the natural local problem is not an eigenvalue problem.